Separation of the main flavonoids and essential oil from seabuckthorn leaves by ultrasonic/microwave-assisted simultaneous distillation extraction - Chunying Li; Jingjing Zhang; Chunjian Zhao; Lei Yang; Wenyan Zhao; Hongwei Jiang; Xueting Ren; Weiran Su; Yuzheng Li; Jiajing Guan (Royal Society Open Science, 2018)
Volatile essential oils (EOs), non-volatile rutin (RU), quercetin (QU), kaempferol (KA) and isorhamnetin (IS) were effectively extracted and isolated from seabuckthorn (Hippophae rhamnoides L.) leaves by ionic liquid-based ultrasound/microwave-assisted simultaneous distillation extraction (ILUMASDE). After optimization by response surface methodology, EOs, RU, QU, KA and IS were separated under the following optimum conditions: an ionic liquid of 1.0 M 1-butyl-3-methyl imidazole bromine salt ([C4mim]), liquid/solid ratio of 12 ml g−1, extraction time of 34 min, microwave power of 540 W and a fixed ultrasonic power of 50 W. Under the optimized conditions of ILUMASDE, the extraction yields of RU, QU, KA, IS and EOs were 9.18 ± 0.35, 5.52 ± 0.23, 3.03 ± 0.11, 5.64 ± 0.24 mg g−1 and 0.095 ± 0.004%, respectively. The yield of EOs obtained using ILUMASDE was 1.07-fold higher than that obtained by conventional hydrodistillation extraction (HDE). In addition, the components of the EOs obtained using ILUMASDE and HDE were similar. The extraction yields of RU, QU, KA, IS obtained by ILUMASDE were 1.03–1.35-fold higher than that obtained by the ethanol ultrasonic-assisted extraction (EUAE), ionic liquid-based ultrasonic-assisted extraction (ILUAE) and ionic liquid-based microwave-assisted extraction (ILMAE). And the extraction time used by ILUMASDE was 34 min, which is 14.17%, 56.67%, 56.67% and 85.00% less than those used by HDE, EUAE, ILUAE and ILMAE, respectively. Therefore, ILUMASDE can be considered a rapid and efficient method for extracting flavonoids and EO from seabuckthorn (Hippophae rhamnoids L.) leaves.